Sistem Informasi Penjadwalan Mata Pelajaran Pada Sma Negeri 02 Tebing Tinggi Dengan Menggunakan Metode Genetika Berbasis Web - Ryandi Apriando; Kurniati Kurniati (Jurnal Pengembangan Sistem Informasi dan Informatika, 2022)
The subject scheduling information system is one way to overcome the optimization problem determined by the institution where the schedule is used, namely at SMA Negeri 2 Tebing Tinggi, Empat Lawang Regency, South Sumatra Province. The software was tested on several different data groups using the genetic algorithm method. The results obtained are helping to arrange automatic scheduling of subject scheduling. Based on the test results of the subject scheduling information system software at SMA Negeri 2 Tebing Tinggi using the Black box and the usability of the overall test summary results are said to be good. So that with the subject scheduling system at SMA Negeri 2 Tebing Tinggi, Empat Lawang Regency, South Sumatra Province, it can be more efficient and even better in compiling subject schedules. Keywords: Information System, Scheduling, Genetics, PHP